The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3906/biy-1504-19
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation with a 130-mT magnetic field improves growth and biochemical parameters in lupin (Lupinus angustifolius L.)

Abstract: The influence of magnetic field stimulation (MFS) on plants is a subject of intense research. The influence of MFS on plants varies depending on its intensity, time of exposure, and form of application. Weak MFS has beneficial effects on physiological and biochemical processes in plant tissues. Lupins (Lupinus spp.) are economically and agriculturally important plants used mainly in livestock feeding or in human consumption. The effects of a stationary magnetic field (130 mT) on the mitotic activity and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…These findings underline the fact that the carotenoid profiles vary considerably among different lupin species and subspecies. In line with the results gained by Mroczek-Zdyrska et al ( 2016 ) in 14-day-old lupin leaves, chlorophyll a concentration always exceeded the total carotenoid and the chlorophyll b concentration in pea and lupin microgreens and leaves (Tables 3 , 4 ). A high chlorophyll a concentration was also described in various green vegetables such as broccoli ( Brassica oleracea var.…”
Section: Resultssupporting
confidence: 88%
“…These findings underline the fact that the carotenoid profiles vary considerably among different lupin species and subspecies. In line with the results gained by Mroczek-Zdyrska et al ( 2016 ) in 14-day-old lupin leaves, chlorophyll a concentration always exceeded the total carotenoid and the chlorophyll b concentration in pea and lupin microgreens and leaves (Tables 3 , 4 ). A high chlorophyll a concentration was also described in various green vegetables such as broccoli ( Brassica oleracea var.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, a significant difference was found between old and young alfalfa plants, with the young alfalfa returning decidedly higher concentrations of chlorophyll a when compared to the old plants. In a study on the effect of a constant magnetic field on the content of chlorophyll a in lupine, an increase of 28% was reported relative to the control [52].…”
Section: Resultsmentioning
confidence: 98%
“…Mroczek-Zdyrska et al 48 observed a similar increase (13–22%) in the content of protein in the sprouts and roots of lupin grown from seeds stimulated with a 130 mT magnetic field. Furthermore, Asghar et al 37 observed that the concentration of protein and chlorophyll increased in the seeds and seedlings of soy after magnetic field and laser light stimulation.…”
Section: Resultsmentioning
confidence: 68%
“…Before sowing, soy seeds were subjected to stimulation using an alternating magnetic field (magnetic induction B = 30mT for t = 60 s) 47 , constant magnetic field (magnetic induction B = 130mT for t = 17 h) 48 and alternating electric field (intensity E = 5 kV/cm for t = 60 s) 39 , 40 (Figs. 1 and 2 ), respectively designated as: AMF, CMF, and AEF as well as C—control sample (non-stimulated seeds).…”
Section: Methodsmentioning
confidence: 99%